A Pediatric Patient With Ascites, Proteinuria, and Thrombocytopenia: A Rare Presentation for a Common Illness. Issue 12 (29th December 2021) - Simpson, Samantha L.; Clarkston, Kathryn; Wurster Ovalle, Victoria M.; Reed, Jennifer L.
Abstract: A 7-year-old female patient presented to our pediatric emergency department with 5 days of fever, sore throat, abdominal pain, vomiting, headache, and 2 days of periorbital swelling. Her initial laboratory evaluation revealed a negative monospot test, neutropenia, atypical lymphocytosis, and thrombocytopenia in addition to transaminitis and proteinuria. An abdominal ultrasound obtained identified hepatosplenomegaly, moderate ascites, acalculous cholecystitis, and a distended appendix with periappendiceal fluid. She was admitted to gastroenterology for further management with antibiotics and surgery and hematology consults. Ultimately, Epstein-Barr virus polymerase chain reaction was positive. This case highlights an atypical presentation of Epstein-Barr virus and the collaborative approach to diagnosis.